2012
DOI: 10.4238/2012.october.11.1
|View full text |Cite
|
Sign up to set email alerts
|

Structure and polymorphism of 16 novel Y-STRs in Chinese Han Population

Abstract: ABSTRACT. Y-chromosome short tandem repeats (Y-STRs) are useful tools for identifying paternity origin and male-female mixed samples because of their male-specificity, haploid inheritance and relatively simplicity. We focused on novel Y-STRs deposited in the human Genome database from DYS708 to DYS726. We typed 16 malespecific Y-STRs from males of a Chinese Han population residing in Shanxi Province (north China), including DYS708-719, DYS721-723, and DYS726, but failed in typing DYS720, DYS724 and DYS725. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…Three of those markers had only population data and no mutation data previously reported: DYS711 (Leat et al, 2007;Maybruck et al, 2009;Zhang, Yang, Niu, & Guo, 2012); DYS712; DYS713 (Leat et al, 2007;Liu et al, 2019;Maybruck et al, 2009;Zhang et al, 2012). For one of the previously discovered Y-STR markers, DYS724, mutation data were previously inferred from population data (Chandler, 2006) and later from deep-rooted pedigrees (Boattini et al, 2019;Claerhout et al, 2018), while mutation data from comprehensive father-son pair analysis as in the present study were not previously reported.…”
Section: Mutation Analysismentioning
confidence: 54%
See 3 more Smart Citations
“…Three of those markers had only population data and no mutation data previously reported: DYS711 (Leat et al, 2007;Maybruck et al, 2009;Zhang, Yang, Niu, & Guo, 2012); DYS712; DYS713 (Leat et al, 2007;Liu et al, 2019;Maybruck et al, 2009;Zhang et al, 2012). For one of the previously discovered Y-STR markers, DYS724, mutation data were previously inferred from population data (Chandler, 2006) and later from deep-rooted pedigrees (Boattini et al, 2019;Claerhout et al, 2018), while mutation data from comprehensive father-son pair analysis as in the present study were not previously reported.…”
Section: Mutation Analysismentioning
confidence: 54%
“…The previously discovered Y‐STRs were: DYS713 (Leat, Ehrenreich, Benjeddou, Cloete, & Davison, 2007), later also described as DYS685 (Maybruck, Hanson, Ballantyne, Budowle, & Fuerst, 2009); DYS711 (Leat et al, 2007), later also described as DYS688 (Maybruck et al, 2009); DYS712 (Leat et al, 2007); and CDY (included in commercial products of FamilyTreeDNA), later also described as DYS724 (Jacobs et al, 2009). Three of those markers had only population data and no mutation data previously reported: DYS711 (Leat et al, 2007; Maybruck et al, 2009; Zhang, Yang, Niu, & Guo, 2012); DYS712; DYS713 (Leat et al, 2007; Liu et al, 2019; Maybruck et al, 2009; Zhang et al, 2012). For one of the previously discovered Y‐STR markers, DYS724, mutation data were previously inferred from population data (Chandler, 2006) and later from deep‐rooted pedigrees (Boattini et al, 2019; Claerhout et al, 2018), while mutation data from comprehensive father–son pair analysis as in the present study were not previously reported.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to autosomes, however, the genetic variety on the Y chromosome has appeared to be relatively low due to the lack of recombination [5,6]. Therefore, more markers or advanced techniques for extracting more genetic information (e.g.…”
Section: Introductionmentioning
confidence: 98%